2022
DOI: 10.1177/10790632221120013
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Developmental Correlates of Paraphilic and Normophilic Sexual Interests

Abstract: The classification of sexual fantasies and behaviors (here referred to as ‘sexual interests’) has historically been divided into ‘paraphilic’ and ‘normophilic’. However, studies on paraphilic interests are often limited to clinical or forensic samples and normophilic interests are rarely assessed in tandem. Previous research has found mixed results for psychological and other correlates of sexual interests, potentially due to inconsistency in operationalism and measurement of fantasies and behaviors. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Since all these items reflected non-paraphilic content, we termed this factor normophilic sexual fantasies. This aligns with the DSM-5’s normophilic versus paraphilic classification system, which, according to Brown et al ( 2022 , 2023 ), avoids labeling sexual fantasy content in frequency terms (typical vs. atypical), offending terms (deviant vs. non-deviant), or culturally-bound terms (normative vs. non-normative). The second factor is a perfect replication of the 17-item sexualized aggression factor by Bartels and Harper.…”
Section: Resultsmentioning
confidence: 54%
“…Since all these items reflected non-paraphilic content, we termed this factor normophilic sexual fantasies. This aligns with the DSM-5’s normophilic versus paraphilic classification system, which, according to Brown et al ( 2022 , 2023 ), avoids labeling sexual fantasy content in frequency terms (typical vs. atypical), offending terms (deviant vs. non-deviant), or culturally-bound terms (normative vs. non-normative). The second factor is a perfect replication of the 17-item sexualized aggression factor by Bartels and Harper.…”
Section: Resultsmentioning
confidence: 54%
“…In addition, various studies have demonstrated that Dark Tetrad traits are linked to an increased likelihood of developing paraphilic interests and behaviors 11 . The four constructs share characteristics of manipulation, callousness, lack of empathy and deceitful behavior 8 , but also contain unique features that seem to be distinctively related to paraphilic interests and behaviors 12 , 13 .…”
Section: Dark Tetrad Personality Traits and Deviant Sexual Interests ...mentioning
confidence: 99%